Ru and W isotope systematics in ocean island basalts reveals core leakage - Nils Messling; Matthias Willbold; Leander Kallas; Tim Elliott; J. Godfrey Fitton; Thomas Müller; Dennis Geist (Nature, 2025)
Abstract The isotopic composition of lavas associated with mantle plumes has previously been interpreted in the light of core–mantle interaction, suggesting that mantle plumes may transport core material to Earth’s surface1–5. However, a definitive fingerprint of Earth’s core in the mantle remains unconfirmed. Precious metals, such as ruthenium (Ru), are highly concentrated in the metallic core but extremely depleted in the silicate mantle. Recently discovered mass-independent Ru isotope variations (ε 100Ru) in ancient rocks show that the Ru isotope composition of accreted material changed during later stages of Earth’s growth6, indicating that the core and mantle must have different Ru isotope compositions. This illustrates the potential of Ru isotopes as a new tracer for core–mantle interaction. Here we report Ru isotope anomalies for ocean island basalts. Basalts from Hawaii have higher ε 100Ru than the ambient mantle. Combined with unradiogenic tungsten (W) isotope ratios, this is diagnostic of a core contribution to their mantle sources. The combined Ru and W isotope systematics of Hawaiian basalts are best explained by simple core entrainment but addition of core-derived oxide minerals at the core–mantle boundary is a possibility.